Molecular Characterization and Homology Modeling of Intercellular Adhesion Regulatory (IcaR) Proteins in Biofilm-Producing Staphylococcus Species - Cunanan, Donmig Jaula; Gonzalvo, Patricia Cristina Noora; Gochuico, Matthew Lauren Cumigad; Falzado, Charlotte Diane Villareal; Cruz, Acelah Estrada; Dejapa, Emmanuel Pastolero; Godin, Chloe Reyna Mae Ybañez; Fenix, Trisha Nicole Reyes; Lirio, Mary Rose Ferrer (Asian Journal of Biological and Life Sciences)
Background: Despite the threat biofilms pose to inpatient care, there is a lack of investigations towards the IcaR protein that regulates the intercellular adhesion locus, which contributes to biofilm formation via polysaccharide intercellular adhesin synthesis. Aim: Since only IcaR proteins of S. aureus and S. epidermidis have been experimentally determined, the study aimed to produce theoretical yet realistic models of other relevant Staphylococcus species (S. xylosus, S. haemolyticus, S. argenteus, S. saprophyticus, S. caprae, and S. capitis) to further understand their functional capabilities in biofilm formation. Materials and Methods: IcaR protein sequences retrieved from NCBI GenBank were subjected to physico-chemical profiling using ProtParam (ExPASy), secondary structure determination through SOPMA, and homology modeling using SWISS-MODEL, i-TASSER, and Phyre2. The best models determined via Ramachandran Plot analysis were refined through the GalaxyWEB server. The models were visualized and analyzed with RCSB Molstar. Results: The IcaR proteins of S. aureus, S. saprophyticus, and S. argenteus displayed similar biofilm regulatory functions. In contrast, S. epidermidis, S. caprae, S. haemolyticus, S. xylosus, and S. capitis are exceptionally homologous, suggesting similar ica Operon regulations. The conserved structures were proportional to their lineage proximity in the Phylogenetic tree. The N-terminal had retained most of its homology while the C-terminal region has produced the greatest variations between the selected Staphylococcus species, indicating variation in dimer stability and ligand susceptibility. Conclusion: The theoretical data generated by this study enhances the existing literature on biofilm regulation. Such knowledge can be applied to develop interventions that target biofilm-related nosocomial infections.
Keywords: Biofilm; Homology Modeling; IcaR Protein; Molecular characterization; Staphylococci.